The experiences of international nurses and midwives transitioning to work in the UK: A qualitative synthesis of the literature from 2010 to 2019. (October 2020) - Bond, Samuel; Merriman, Clair; Walthall, Helen
Abstract: Purpose: In recent years there has been an increase in international nurses and midwives (trained outside of the European Economic Area) recruited to work in the UK. The aim of this review was to synthesise the most recent qualitative research exploring the experiences of international nurses and midwives as they transition and adapt to living and working in the UK. Findings: A systematic literature search using the databases psycINFO, CINAHL, MEDline, Web of Science, as well as Google Scholar, resulted in six studies meeting the criteria of primary qualitative research published since 2010 and focussing on the UK as the host country. A lack of research into the experiences of midwives meant that the participants in each of these six studies were international nurses. The findings of these six studies were synthesised into 4 analytical themes: (1) Cultural integration; (2) Individual challenges; (3) Support networks, and; (4) Communication issues. Participants reported difficulties adapting to their new life in the UK, including within their role as a nurse, but also in finding and building positive relationships that would help to ease their transition. Instances of discrimination, an undervaluing of international nurses' skillset, and problems around communication were all detrimental to this process. Summary: These studies are in line with earlier findings that suggest international nurses face a challenging integration process when recruited to work in the UK, indicating no improvement in international nurse experience. With an increasing number of international nurses being recruited to work in the UK, this review raises concerns based on the need to effectively support these nurses to successfully integrate into work and the wider society.